The Effects of Perceived Social Support and Self-worth on Depressive Symptomatology in Children with and without Developmental Coordination Disorder (DCD) - Francis, Mona; Piek, Jan (The Australian Psychological Society Ltd, 2003)
Halter's (1987) model of the relatioship between self worth and depression was utilised in the present study as a basis for investigating the unique impact that self- perceptions of competency and perceived social support have on the level of self worth and depressive symptomatology perceived by school-age children with and without Developmental Coordination Disorder (DCD: American Psychiatric Association, 1994).Forty girls and forty two boys, assigned to matched pairs, were assessed on their level of motor coordination using the McCarron Assessment of Neuromuscular Development (MAND) (McCarron, 1997), their level of perceived social support using the Social Support Scale for Children(SSSC) (Harter, l985a), the nature of their self- perceptions, including self-worth,by the Self-Perception Profile for Children (SPPC) (Harter, 1985b),and their perceived level of depressive symptomatology using the Children's Depression Inventory (CDI) (Kovacs, 1992). The findings of the research indicate that children with DCD perceived higher levels of depressive symptomatology when compared to children without motor coordination problems. The implications of these findings are discussed with particular emphasis placed on possible factors that could be incorporated into early intervention strategies aimed at preventing depressive symptomatology from occurring in young children with DCD.